GAMBARAN PERILAKU DIET PENURUNAN BERAT BADAN ANGGOTA FITNESS CENTER NEW LIFE GYM LIPPOMALL MEDAN - Syafiah Mukhlishoh; Albiner Siagian; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The society efforts to get the ideal body are more increase. This is evident from the number of people who signed up at the gym (fitness center) as a member and then applying a weight loss diet once during fitness training. But the results obtained from practicing fitness and weight loss dietary practices are not in line with expectations even dangerous to health. The purpose of this study was to representation the weight loss dietary behavior of the New Life Gym members in Lippomall Medan. The results showed that members of the New Life Gym knowledge about weight loss diet is quite as many as 48.2%. Member New Life Gym attitude about weight loss diet is good, that as much as 49.4%. Action / practice of weight loss diets member New Life Gym is good as many as 63.6%, this is evidenced by the many members of the New Life Gym healthy diet weight loss. There is no significant relationship between knowledge and attitude to weight loss diets action member New Life Gym. Fitness center members need to have a good knowledge before making a weight loss diet. A good knowledge about weight loss is necessary to make decisions kind of weight loss diet such as what should be done according to body weight or BMI member fitness center. Keywords: Dietary Behavior, Weight Loss, Fitness Center Members